"neurolinguistics And The Programming Of The Human Mind" - .ghilous, salah; .arioua, imane (El Omda in Linguistics and Discourse Analysis, 2026)
Neurolinguistics provides a scientific basis for understanding how the brain processes language and how this affects thinking, emotions, and behavior. Research shows that language is more than just a means of communication; it acts as a neurological stimulus that can reorganize neural networks and enhance both cognitive and emotional flexibility. Language programs the human mind through several mechanisms, including cognitive reframing to turn negative thoughts into positive ones, guided repetition to strengthen neural pathways linked to desired knowledge and behaviors, and storytelling and metaphors to consolidate information and connect it with emotions. These processes support better decision-making, adaptability, and self-regulation, making neurolinguistics a powerful tool for shaping thought, regulating emotions, and guiding behavior, ultimately contributing to a balanced and continuously developing mind